Effectiveness of The Educational Leadership Program in Developing Professional and Leadership Competencies of Secondary School Principals In Wadi Al-Seer District, Jordan - Al-Harby, Seetah Ali (Journal of Educational and Psychological Sciences, 2020)
The aim of study to revel the Effectiveness of The Educational Leadership Program in Developing Professional and Leadership Competencies of Secondary School Principals in Wadi Al-Seer District, Jordan. The study based on the description approach which based on the descriptive method researcher used a questionnaire which consist of (51) items to analyze and process data divided into four areas. The total degree of Education Leadership Program of areas directorate principals was high. study population was composed of all principals (68) which account for all the principals of secondary schools of The In Wadi Al-Seer District study sample consist of(20) male principals and(40) female principals .This sample was chosen randomly. The result showed that the level of Effectiveness was high and The finding also showed there are no statistically significant differences between the level of principals sex (male and female) in addition there were statistically significant differences between principals of (less than 5 years) of experience and these with (10 and more) years of experience in favor of the second group and statistically significant differences between teachers of (10+) years of experience and these with (10 and more) years of experience in favor of the second group. In light of these findings the researcher suggested a set of recommendations including the necessity of considerate the years of experience of principals during evaluation and take advantage of the educational leadership program to select principals to the scale of educational leadership effectiveness.
Keywords: Effectiveness; Competencies; Educational Leadership Program